Effect of financial development on foreign direct investment in Sub-Saharan African countries - Anyalagbu, Cyprian S.; Okafor, Reuben Izuchukwu; Obi, Cyril Ogugua (Journal of Law, Economics, and Engineering, 2026)
This study examined the impact of financial development on foreign direct investment (FDI) inflows in 20 Sub-Saharan African (SSA) countries from 2007 to 2024. Anchored on the Mankiw et al. (1992) endogenous growth model, the research evaluates how banking access, market depth, and institutional frameworks influence international capital. Using annual panel data (2007–2024) from 20 Sub-Saharan African countries, the research employs a two-step System GMM estimator to address endogeneity and heterogeneity. Key variables include FDI, institutional quality, and the Human Development Index. Pre-estimation diagnostics like the Bond and Pesaran tests ensure model integrity, while Hansen and Arellano-Bond tests verify instrument validity and consistency. System GMM analysis confirms that FDI in Sub-Saharan Africa is self-reinforcing, with a lagged coefficient of 0.37 (p < 0.01). Financial institution access promotes inflows (0.0317, p < 0.01), while institutional quality proves decisive (0.3284, p < 0.01). Conversely, financial market depth (-0.0390, p < 0.10) and human development (-6.7156, p < 0.01) show negative effects, suggesting that volatility and rising labor costs deter certain investments. Diagnostics, including a Hansen p-value of 0.740 and AR2 of 0.216, confirm the model's high reliability for policy formulation. The study concludes that while financial access and strong governance are essential for attracting FDI, SSA nations must transition from labor seeking to skill seeking investment models. Enhancing financial regulations alongside institutional reforms is critical to transforming financial development into a sustainable mechanism for attracting high quality foreign capital.